The Impact of Web-Based Language Teaching on Advanced EFL Learners’ Self-Regulation and Self-Actualization - Fadaei, Homa; Dashtestani, Reza (AJELP: Asian Journal of English Language and Pedagogy, 2023)
This quantitative research has been prepared to study the effect of web-based language teaching on advanced EFL learners’ self-regulation and self-actualization. In doing so, 40 advanced students of both genders were chosen based on the convenience sampling method. They were approximately between eighteen to twenty-eight years of age at a private language institute in Kerman, Iran. Different instructional and testing materials, including the Oxford Placement Test, Short Index of Self Actualization Inventory, and Academic Self-Regulation Questionnaire were applied to gather the required data. Results revealed a significant improvement in self-regulation and self-actualization of the students in the case group. It means E-learning had an impact on advanced EFL learners’ self-regulation and self-actualization. The results of this work could be beneficial for educators, trainers, instructors, and material developers to take into account the efficacy of such instructional materials and devote greater resources to developing and implementing them.